Digitizing migration heritage: A case study of a minority museum - Randi Marselis (MedieKultur: Journal of Media and Communication Research, 2010)
Museums are increasingly digitizing their collections and making them available to the public on-line. Creating such digital resources may become means for social inclusion. For museums that acknowledge migration history and cultures of ethnic minority groups as important subjects in multiethnic societies, digitization brings new possibilities for reaching source communities. This article describes Web projects conducted at Museum Maluku in Utrecht, the Netherlands. The article focuses on the museum’s experiences with cross-institutional Web projects, since digitization of the museum’s collection was initiated through collaboration with major national heritage institutions. The article also discusses how source communities through digital participation can become involved in building cultural heritage. Based on the case study of the Museum Maluku, it is argued that in order to design an appropriate mode of user participation as well as a sense of ownership it is crucial to take memory politics of source communities into account.